World heritage listed sites - does it attract tourists? a study of factors influencing Norwegian tourist's intention to visit Unesco's world heritage listed sites - Robinson, Kristina (Universitetet i Nordland, 2015)
Masteroppgave i i bedriftsøkonomi - Universitetet i Nordland, 2015